The counselor is a professional not dispensable for educational education (Journal of Parents and Teachers, 2012)
This article presents the importance of introducing and recognizing the work of professionals in psychology, pedagogy and social work. Several articles are presented in this issue in relation to one of the functions of the educational advisor, which is psychopedagogical evaluation.
Keywords: Educational counselor; psychology; pedagogy; social work; psychopedagogical evaluation; LOGSE.